Transcriptome reveals the roles and potential mechanisms of CeRNA in the regulation of salivary gland development in the tick Rhipicephalus haemaphysaloides - Hu, Shanming; Chen, Songqin; Zhu, Haotian; Wang, Yanan; Zhou, Yongzhi; Cao, Jie; Zhang, Houshuang; Zhou, Jinlin (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionThe salivary glands of female ticks rapidly degenerate after feeding. The mechanism involves programmed cell death mediated by an ecdysteroid receptor. A competing endogenous RNA (ceRNA) network has been established using miRNA and the competitive binding of three types of RNA (lncRNA, circRNA, and mRNA), that were demonstrated to be involved in the regulation of biological processes. However, the comprehensive expression profile and competing endogenous RNA (ceRNA) regulatory network between mRNAs and ncRNAs involved in salivary gland development remain unclear.MethodsIn the current study, we employed whole-transcriptome sequencing (RNA sequencing) at various stages of feeding to identify differentially expressed lncRNAs, circRNAs, miRNAs, and mRNAs. The ceRNA networks combining lncRNAs, circRNAs, miRNAs, and mRNAs were predicted and constructed based on the miRanda and TargetScan databases. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses were performed for target mRNAs with significantly different expression levels.ResultsWe identified several pathways related to organ growth and development: Insulin secretion, the Hippo signaling pathway, the Pl3K-Akt signaling pathway, the FoxO signaling pathway, and the Ferroptosis pathway in the lncRNA-miRNA-mRNA network, and Steroid biosynthesis, Cholesterol metabolism, the FoxO signaling pathway, and the Ferroptosis pathway in the circRNA-miRNA-mRNA network, each of which involved insulin and ecdysteroid regulation.DiscussionOur findings have advanced our understanding of the underlying mechanisms of salivary gland development and degeneration.